Biosurfactants in Food - Sharma, Deepansh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The present work aims to cover the perspectives of biosurfactants, which can be of interest in food-related industries and biomedical applications. Biosurfactants are a structurally diverse group of surface-active molecules extensively produced by bacteria, yeast and fungi. Despite having significant potential associated with emulsion formation, anti-adhesive and antimicrobial activities, considerably few applications have been reported regarding applications of biosurfactants in food formulations and processing. The utilization of biosurfactants, which are highly functional in food and biomedical applications, has become more and more significant. Along with providing an overview of biosurfactant properties, the book suggests how these properties could be applicable in the food industry.
Introduction -- Classification and properties of biosurfactants -- Application of biosurfactants in food -- Future prospects.
Keywords: Food -- Microbiology; Food science; Industrial microbiology; Food Microbiology; Food Science; Industrial Microbiology